Design Of A Geographic Information System For Mapping Crime-Prone Areas In The City Of Pinang Web-Based - Kurniawan, Ardi Ari; Aji, Agung Prasetyo; Firmanto, Tudi; Fadhil, Ahmad (CV. Digital Innovation, 2024)
One of the information systems that can help map an area is a Geographic Information System (GIS). GIS helps researchers, managers, and decision makers in solving problems, one of which can be implemented in mapping crime-prone areas. Crimes that often occur in the jurisdiction of the Kota Pinang Police Station are persecution and beatings, bullying, theft, fraud and so on. Because there is no GIS that can map existing crime-prone locations, so that people are still looking for criminal location information through the nearest police station and the police are still recording criminal cases manually. So a geographic information system was built that can map crime-prone locations in the Kota Pinang Police Station using the Rapid Application Development (RAD) method. The main feature of this geographic information system is to display the number of crime points based on the year and the location of crime-prone areas. The test results obtained, recorded 58 types of crime at 12 crime-prone points in the Kota Pinang area in 2024. With this web-based Geographic Information System, the police can easily record crime-prone areas, as well as the general public who want to know the crime-prone areas by simply looking at the data contained in this system.